Digital Ethnography: A Systematic Literature Review - Delli Paoli, Angela; D’Auria, Valentina (Italian Sociological Review, 2021)
Digital ethnography can be defined as a contemporary form of ethnography which considers online social spaces of discussion following the advances in data transmission technology. In the last few years, various attempts of considering online spaces in ethnographic research have been made producing different styles of online ethnography, each identified by a different label. This paper aims to provide a systematic review of the topic to map the practice of digital ethnography. The research process followed four key steps: search, selection, analysis and synthesis. In the search phase, we searched contributions iteratively in Web of Science and Scopus by using a variety of keywords corresponding to the different labels used to refer to digital ethnography. In the selection phase, we adopted a selective stance that aims to provide a critical review of the existing research and practices in the context of digital ethnography. In the analysis phase, we carried out a content analysis of the papers combining deductive and inductive coding. The synthesis phase involves a process of typology development to pragmatically reduce and systematize an extensive set of features and digital ethnography practices. Basing on the type of data collected (Small vs Big Data) and the type of fieldwork (meta or contextual field), we detected four types of ethnographic research: social media ethnography, contextual digital ethnography, meta digital ethnography, cross-media ethnography.